1996
DOI: 10.1159/000126964
|View full text |Cite
|
Sign up to set email alerts
|

Arachidonic Acid-Induced Hormone Release in Somatotropes: Involvement of Calcium

Abstract: Arachidonic acid (AA) has been implicated in signaling actions in several cell types including endocrine cells. In the present study, we investigated the effect of exogenous AA on GH release from dispersed pituitary cells and tried to elucidate the mechanism involved in this process. We show that AA stimulates GH release in a dose- and extracellular calcium-dependent manner. The effects of AA on cytosolic calcium concentration ([Ca2+]i) were studied using dual-emission microspectrofluorim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 13 publications
2
7
0
Order By: Relevance
“…Our observations that arachidonic acid (AA) induces calcium influx in Jurkat T-cells are in accordance with the reports of several investigators who have shown that this fatty acid induces calcium influx in different cell lines [17,[28][29][30][31]. To shed light on whether exogenous AA evoked capacitative calcium influx, we employed thapsigargin (TG) and conducted experiments in 0% Ca 2+ buffer.…”
Section: Discussionsupporting
confidence: 90%
“…Our observations that arachidonic acid (AA) induces calcium influx in Jurkat T-cells are in accordance with the reports of several investigators who have shown that this fatty acid induces calcium influx in different cell lines [17,[28][29][30][31]. To shed light on whether exogenous AA evoked capacitative calcium influx, we employed thapsigargin (TG) and conducted experiments in 0% Ca 2+ buffer.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, the inhibition of PLA 2 activation by chemical inhibitors and siRNA curtailed the TGinduced Ca 2+ influx in CD36-positive TBCs. These observations suggest that AA (exogenous or endogenous) evokes Ca 2+ influx in these cells as shown elsewhere (34,35), and its action on Ca 2+ influx is not influenced by its metabolites (36).…”
Section: Discussionsupporting
confidence: 72%
“…The inhibitory effect of arthritis on GH does not seem to be mediated by the increased release of PGE 2 , since this prostanoid has been reported to be a GH secretagogue (12,43). A stimulatory effect of lipoxygenase products on pituitary GH synthesis and secretion has also been reported (12,53). Therefore, the inhibitory effect of arthritis on pituitary GH can be secondary to another inhibitory substance that is released after COX-2 activation.…”
Section: Discussionmentioning
confidence: 90%